Qualitative and quantitative analysis of nanoparticles using laser-induced breakdown spectroscopy (LIBS) and energy dispersive x-ray spectroscopy (EDS). (25th September 2019) - Iqbal, T; Ejaz, A; Abrar, M; Afsheen, S; Batool, S S; Fahad, M; Tahir, M B
Abstract: The quantitative and qualitative investigation of silicon dioxide ( ) and cobalt titanate ( ) nanoparticles was performed using laser-induced breakdown spectroscopy (LIBS). The optical emission spectra obtained from the laser ablation of nanoparticles were analyzed for all the observed transitions for constituent elements of the target materials. It was found from the spectral lines that Ca, Mg, Na, Co, Ti, O and Si along with a few minor elements are present in different proportions. The concentration of each element in these nanoparticles was evaluated using the corresponding spectral lines. Plasma parameters such as electron temperature and electron number density were calculated from the Boltzmann plot method and Stark broadening of neutral spectral lines, respectively. Energy dispersive x-ray spectroscopy (EDS) and scanning electron microscopy are employed to check the composition of the elements and the surface morphology, respectively. The concentrations of observed elements from the nanoparticles using LIBS are then compared with EDS analysis. The results obtained from both techniques are in good agreement with each other.